Religions and Cultural Practices: Conflict with Law or Human Rights - Khosa-Nkatini, Hundzukani P.; Mbiada, Carlos Joel Tchawouo (KAMASEAN: Jurnal Teologi Kristen, 2024)
South Africa is guided by the Constitution which entrenches equality among citizens, regardless of gender, race, religion or political affiliation. In the same vein, the Constitution also recognizes the right to practise one’s religion and culture. Religious and cultural practices must respect the diversity of the society. Such respect must also be observed within the community and religious spectrum. It is in this perspective that this paper investigates whether religious and cultural practices are carried out equally within the Black community. The authors, through a review of literature and observations carried out within the Black community, found systemic violations and discriminatory practices between men and women. The authors found that women are being subjected to abuse in the name of culture and that some practices, such as cleansing ceremonies, violate their dignity. The authors recommend a degree of fairness in cultural practices and that both genders should be subjected to the same practices or treated equally.